Income Efficiency Of Cassava Farming In Ciseeng Sub-District Bogor Regency - Lola Rahmadona; Rizka Endah Agustin (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2021)
Cassava is the third food crops in Indonesia after rice and maize. Ciseeng Subdistrict selected as the study site because it is one of the centers of cassava production in Bogor Regency. The method used is mixed methods and its implementation using survey techniques. Respondents determined intentionally (purposive) with a total of 30 farmers. Declining interest of farmers is a problem in the cassava farming activities in Ciseeng Subdistrict. The purpose of this study was to determine the characteristics and efficiency of cassava farming income in Ciseeng Subdistrict. In this study the characteristics described in the descriptive and efficiency of farming income using analysis of R/C ratio. The results of the analysis showed that the income from cash costs and total costs on cassava farming in Ciseeng Subdistrict has a value greater than zero. Revenue from cash costs is IDR 17.162.017,14 per hectare and for total costs is IDR 7.901.952,86 per hectare. The results of the R/C ratio analysis also showed that cassava farming in Ciseeng Subdistrict was worth more than one. The R/C ratio of cash costs is 2,45 and the total costs are 1,38. So it can be said that cassava farming in Ciseeng Subdistrict is efficient or feasible to be developed.